Revitalisasi Tradisi Kebo Keboan di Era Digital Menguatkan Nilai Islam dan Kearifan Lokal untuk Harmoni dan Toleransi - Biati, Lilit; Suprapto, Ribut; Mamlukhah, Mamlukhah; Obianto, Agung (Proceedings of Annual Conference for Muslim Scholars, 2024)
This research explores the revitalization of the Kebo-Keboan tradition in Alasmalang Village, Banyuwangi, in the digital era, focusing on its role in enhancing Islamic values and local wisdom for promoting harmony and tolerance. The aim is to analyze how digital platforms can preserve this cultural heritage while integrating Islamic teachings, such as gratitude and social unity, within the local community. The study uses a qualitative approach, involving direct observation, interviews, and content analysis of the tradition's representation in digital media. Results show that the digital promotion of Kebo-Keboan, through social media and online streaming, has increased participation and recognition globally, positively impacting the local economy by attracting tourists. Additionally, it strengthens Islamic values such as collective prayer and community solidarity, while preserving cultural identity. In conclusion, the digital transformation of Kebo-Keboan contributes to sustaining cultural heritage, fostering tolerance, and promoting economic growth, while engaging younger generations in cultural preservation.